Kadali Pushpa Swaras Paan and Kadali Pushpa Ghrita Nasya in the Management of Asrigdara - Sunita; Saxena, Anjana (International Research Journal of Ayurveda & Yoga, 2022)
Menstruation is mirror of reproductive health. Regular menstrual cycles with adequate quantity and duration of bleeding indicate good reproductive health, with variations in these being reflected as menorrhagia, oligomenorrhoea, dysmenorrhoea, PCOS, infertility etc. Incidence of Raktapradara is increasing day by day due to changing life style, increasing stress etc.Data suggests that 10 to 13% of all gynaecological outpatients are of Raktapradar (DUB).According to Ayurvedic literature the aggravated Apanavayu withholds vitiated Rakta which is increased in the amount. It when reaches artavavahasrotas leads to increase in the amount of raja, (here Artavavahasrotas taken as whole female genital organs along with functional axis i.e., H-P-O axis). Altered H-P-O axis and GnRH regulation causes Raktapradara. So a study was done in 3 diagnosed patients of raktapradara to evaluate the effect of kadalipushpaghrutanasya ( Ghee processed with the juice of Banana inflorescence )along with oral kadalipushpa swarasapaana (juice of bnana inflorescence )with dadhi, with the aim to minimize the cyclic blood loss and to Regularize the cycle. Subjective criteria are used to assess the amount of blood loss before and after the treatment. This therapy, helped to cure the heavy flow during menses and regularized the cycle.